Josiah Gould, A Digest of the Statutes of Arkansas, Embracing All Laws of a General and Permanent Character in Force at the Close of the Session of the General Assembly of 1856, at 374-75 (1858) - (:unkn) unknown (My University, 1855)
Prohibited hunting with a gun with intent to kill game or shoot for amusement on the Sabbath day. Violators guilty of a misdemeanor, fined not less than five nor more than twenty-five dollars.
Keywords: HUNTING REGULATION